Analisis Kesalahan Berbahasa Pada Teks Laporan Riset Mini Mahasiswa Universitas Negeri Medan - Firman Matias Simanjuntak; Agus Sibagariang; Thria Damayanti Manullang; Yuni Yolanda Situmorang; Alfonsius Yogbakci; Wisman Hadi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research was conducted to determine various language errors contained in the mini research reports of students of the Indonesian Language and Literature Education Study Program. The method used is a qualitative descriptive method with data collection techniques by means of observation, documentation and literature study. The source of data in this research is a mini research report from students of the Indonesian Language and Literature Education Study Program Class of 2022, 3rd semester in the 2023 Academic Year at Medan State University. Based on the analysis activities that have been carried out, various language errors were found in the areas of phonology, morphology, syntax and semantics.